Grounding to Giving: : ‘From-What’ and ‘To-Whom’ in the Spiritual Exercises of St. Ignatius - Manalili, Michael Mookie C. (Lumen et Vita, 2019)
Through its embodied systematic mysticism, the Spiritual Exercises of St. Ignatius has formed the Jesuit order and countless Ignatian educators. Upon analysis of the Principle and Foundation (§23) in the beginning and the Suscipe (§234) at the end, the movement from the philosophical universal to the particularity of 'this-ness' can be seen. The Principle and Foundation, both etymologically hinting at the prior [Latin: ‘principum’] and the ground [Latin: ‘fundare’], begins with a beautiful cosmology of how the world is oriented towards the return-gift back towards God. However, God is spoken of here in the third-person. Yet, by the time of the Suscipe [English: ‘receive’], the theme is still on the gifted-ness of life and world. However, God is addressed in the second-person here as if face-to-face – the Divine “You”. This movement from the universal to the particular invites the exercitant to gaze into the eyes of Christ Crucified. In doing so, particularly in the Third Week, the exercitant gazes into the iris of God who reflects back the gaze of Love - pointed at those Whom God loves, those in the margins. The Spiritual Exercises thus extends the invitation to incarnate the two-fold nature of the greatest commandment. As it is in the Second Ending of the Book of John, the invitation of gift is extended from the divine Vine to the branches: “Amas me? Pasce oveas meas. Sequere me. // Do you love me? Feed my sheep. Follow me.”